Knowledge and Innovation - Essential Factors for Overcoming the Current Economic Impasse - Ramona Frunza (CES Working Papers, 2010)
Human resource is currently the most valuable wealth of a nation and carries with it the most important principle of development; it is about innovation, without which competitiveness is unthinkable. Romania is part of the “catching–up” group of countries in innovation. In order to assume new responsibilities and to prepare for the competition with other European countries and not only, manyreforms and changes is necessary. Assuming these premises, in this paper, our intention is to analyze the situation of innovation at EUlevel and to see at what chapters our authorities must to work harder to equalize the other states from the Western European states. This thing is absolutely necessary because, now, when our country makes part from EU, it needs to invest in human resources through better education, skills and support.
Keywords: 330; knowledge; innovation; economic impasse; technological change; research